KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH - Kharisma Nawang Sigit; Euis Soliha (Jurnal Keuangan dan Perbankan, 2017)
This study described the effect of product quality and service quality on customer satisfaction and loyalty. The population in this study was the customers of Kredit Usaha Rakyat at BRI Warungasem. The sampling method used in this research was purposive sampling. The samples in this study were 100 customers in People's Business Credit (Kredit Usaha Rakyat) BRI Batang Branch Unit Warungasem who had already taken at least two-time KUR credits. The instrument of answers measurement used was a Likert scale 1-7 alternative answers. The testing instrument used was validity and reliability, and testing the model used was the coefficient of determination and F test (goodness of fit). Testing the hypothesis in this study used t-test. Variables used in the study were product quality, service quality, customer satisfaction, and loyalty. The results showed that there was an effect on product quality and customer satisfaction. Service quality affected customer satisfaction. Product quality affects customer loyalty. The quality of service had an effect on customer loyalty. Customer satisfaction had an effect on customer loyalty.JEL Classification: G21, M21, M31